Anti-mollusk Selectivity of Jayanti Plant (Sesbania sesban L., Merr) for the Control of Golden Snails, a Pest of Paddy - Suripto Suripto; Gunawan, E.R.; Tresnani, G.; Jupri, A. (Jurnal Biologi Tropis, 2021)
Pest control is an essential aspect of rice cultivation. The golden snail (Pomacea speciosa) is one of the pests in rice fields. Damage to rice plants due to golden snail attacks has occurred in several provinces in Indonesia and several countries such as the Philippines, Thailand, Japan, and Malaysia. Various steps to control golden snails have been carried out, both mechanically, biologically, and chemically. However, each biological and mechanical control of golden snails is impractical to apply to very large rice fields. Meanwhile, the control of golden snails using synthetic molluscicides such as Brestan and Dimotrin is minimal because it can pollute the environment and cause the death of fish and the rice plant itself. To suppress the emergence of environmental pollution problems in overcoming this golden snail, natural molluscicides from plant materials are studied. Several plant species have been known to have anti-mollusk properties, one of which potentially is the Jayanti plant {Sesbania sesban (L.) Merr.}. This study aimed to evaluate the anti-mollusk performance of S. sesban for controlling golden snails, a pest of rice plants. The dry powder of S. sesban leaves was extracted in stages with a series of solvents of petroleum ether, chloroform, and ethanol to obtain an extract fraction that was selected as a mollucicide. Each extract fraction produced was tested for its toxicity to the gold snail, carp, rice germination, and rice plant growth. Data on the mortality of golden snail and carp fish, the percentage of germination inhibition, and rice growth were processed by probit analysis, respectively. The outputs of the analysis were LC50 of each extract fraction for golden snails and carp. The ratio of LC50 for golden snail with LC50 for carp indicated each extract fraction's physiological selectivity of anti-mollusk properties. The results showed that the highest lethal toxicity to gold snails was indicated by the extract fraction-ethanol, while to carp, it was indicated by the extract fraction-chloroform. Each extract fraction of S. sesban leaves did not inhibit the germination and growth of rice plants. The extract fraction- ethanol had the highest anti-mollusk selectivity compared to the other two fractions. Bioactive examination showed triterpene saponins from the extract of S. sesban leaves, with the highest relative levels in the ethanol fraction compared to the other two extract fractions.